Atomic-thin WS2 kirigami for bidirectional polarization detection - Liu, Xiao (2024)
The assembly and patterning engineering in two-dimensional (2D) materials hold importance for chip-level designs incorporating multifunctional detectors. At present, the patterning and stacking methods of 2D materials inevitably introduce impurity instability and functional limitations. Here, the space-confined chemical vapor deposition method is employed to achieve state-of-the-art kirigami structures of self-assembled WS2, featuring various layer combinations and stacking configurations. With this technique as a foundation, the WS2 nano-kirigami is integrated with metasurface design, achieving a photodetector with bidirectional polarization-sensitive detection capability in the infrared spectrum. Nano-kirigami can eliminate some of the uncontrollable factors in the processing of 2D material devices, providing a freely designed platform for chip-level multifunctional detection across multiple modules.